Factors Affecting Sustainable Use of Minecraft-based Lessons - Manahan, Dominique Marie Antoinette (Archīum Ateneo, 2023)
This paper examines the factors that affect the sustainable use of Minecraft-based lesson plans. We focus specifically on teachers who received training on using What-If Hypothetical Implementations in Minecraft (WHIMC), a set of Minecraft worlds designed to teach astronomy, geosciences, and ecology. We commissioned a group of teachers to develop lesson plans using at least one of the WHIMC worlds and pilot their implementation in their classes. Another group of teachers received training on developing learning modules with WHIMC but had the freedom to choose when and how to implement their lesson plans during the school year. The teachers cited logistical impediments, scheduling impediments, lack of technical resources, lack of curricular alignment, changes to teaching modalities, limited time for practice, and anxieties about classroom management as barriers to sustainable use of WHIMC. They suggested the training of additional teachers to create a community of practice whose members can collaborate and support each other’s use of WHIMC for STEM education.